Future trends in auditing: preparing for a technology-driven landscape - Muhammad Arnim, Nur Afiqah Najwa; Abd Razak, Siti Noor Azmawaty (Faculty of Accountancy, Universiti Teknologi MARA (UiTM) Cawangan Kelantan, 2024)
The auditing field is changing rapidly with advances in technology, moving to a tech-based environment that auditors need to be ready for. Processes of Audit are changing at an accelerating rate. This change is driven by enablers such as Artificial Intelligence (AI), Machine Learning (ML) Blockchain, Robotic Process Automation (RPA), Big Data Analytics and Cloud computing that have made the traditional audit process obsolete. In summary, utilisation of this technology can be defined as audit firms transitioning from traditional manual efforts to advance systems that in doing so increase the level of accuracy and provide a more complete and informative set of audited information (Atanasovski & Trpeska et al., 2020). There is a shift in what the auditor role now looks like, and these coming technologies will necessitate different skills from auditors, constituting an evolution to professional development that must take place. One of the pressing issues in auditing today is job-displacement caused by technological advancements. Tasks such as data entry, reconciliation and even fundamental analysis can be handled by Automation or AI-driven tools without the requirement of human interference. According to research from the American Institute of CPAs (AICPA) and Chartered Institute of Management Accountants (CIMA), 50% of accounting work could be automated, which is significant streamlining of roles concentrated on routine operations. Still, automation may replace some jobs with others.